2019
DOI: 10.3389/fonc.2019.01117
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IBSP Expression Predicts Poor Prognosis in Patients With Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC), which is characterized by invasiveness and poor prognosis, is the sixth most common leading cause of cancer-related death worldwide. Despite advances in multimodality therapy, ESCC mortality remains high, and an understanding of the molecular changes that lead to ESCC development and progression remains limited. In the present study, Integrin Binding Sialoprotein (IBSP) upregulation was found in 182 of 269 (67.7%) primary ESCC cells at the mRNA level by quantitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…[24][25][26] A majority of SIBLING family members can be primarily detected within bone tissues, a small portion of these proteins show abnormal expression within malignant cancer tissues. 18,27 The aberrantly expressed IBSP gene is tightly associated with an increased risk of malignant transformation, bone metastasis, along with dismal prognostic outcome of non-small cell lung cancer (NSCLC), BC, and PC. 15,17,[28][29][30] There are few reports on the relationship between IBSP and CRC, only a study of regulation of osteopontin and related proteins in rat CC531 CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26] A majority of SIBLING family members can be primarily detected within bone tissues, a small portion of these proteins show abnormal expression within malignant cancer tissues. 18,27 The aberrantly expressed IBSP gene is tightly associated with an increased risk of malignant transformation, bone metastasis, along with dismal prognostic outcome of non-small cell lung cancer (NSCLC), BC, and PC. 15,17,[28][29][30] There are few reports on the relationship between IBSP and CRC, only a study of regulation of osteopontin and related proteins in rat CC531 CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…IBSP has been recognized to be the possible oncogene, which is usually overexpressed and upregulated in numerous cancers, such as prostate cancer (PC), breast cancer (BC), and lung cancer (LC). [17][18][19][20] Only few studies have reported the relationship between IBSP and CRC, and the biological function and molecular mechanism of IBSP involved in CRC progression are completely unknown. The present work measured IBSP expression within CRC samples at mRNA and protein levels through qRT-PCR together with Western blotting analysis.…”
Section: Introductionmentioning
confidence: 99%
“…COL5A1 is associated with the metastasis of LUAD [86]. IBSP overexpression is significantly related to lymph node metastasis in esophageal squamous cell carcinoma [87]. A high expression of COL5A2 is associated with metastasis in renal cell carcinoma [88].…”
Section: Discussionmentioning
confidence: 99%
“… 40 IBSP encodes a specific regulator of matrix metalloproteinase, and high expression of IBSP is correlated with poor prognosis of esophageal carcinoma. 41 However, the role and expression levels of STEAP3 or IBSP have not been explored in renal cell carcinoma. The current study conducted bioinformatics analysis, and the findings showed that STEAP3 and IBSP are highly expressed in advanced renal cell carcinoma and are implicated in EMT, cell cycle regulation, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%